2022
DOI: 10.30699/fhi.v11i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Registration Systems: Current Recommendations and Challenges

Abstract: Introduction: In recent decades, following the upward trend of aging, one out of three people in the world need rehabilitation services during the period of illness or injury. Considering the long-term complications and high costs of treatment, the need to follow up and review the evidence to find the best care programs and extensive planning in this field seems mandatory. Registry systems (registration) in this area can provide the necessary evidence for strategic decisions in this field. Of course, launching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…On the other hand, telerehabilitation is a cost-effective, safe, efficient, and feasible approach. [ 25 26 27 28 29 30 32 39 40 41 42 43 44 45 46 47 48 49 ] The type of telerehabilitation approach was simultaneous in all interventions and did not show a difference in performance or physical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, telerehabilitation is a cost-effective, safe, efficient, and feasible approach. [ 25 26 27 28 29 30 32 39 40 41 42 43 44 45 46 47 48 49 ] The type of telerehabilitation approach was simultaneous in all interventions and did not show a difference in performance or physical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the provision of integrated rehabilitation services requires strong infrastructure, including the minimum set and the ideal set of integrated, valid, and comprehensive data in each of the rehabilitation sub-disciplines. This infrastructure cannot be achieved except by putting together the pieces of the puzzle in an integrated manner, by bringing together similar valid infrastructures in other countries, conducting review studies to collect all available data, and using the opinions and suggestions of experts in each field to finally reach the lofty goal of evidence-based rehabilitation [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have addressed the design of different MDSs or speech therapy information systems, including remote speech therapy based on different MDSs [19][20][21][22][23][24][25][26][27][28][29][30][31]. However, evidence-based speech therapy and the basic need for an integrated system in the initial step require the unification of basic infrastructure, including MDS.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, previous studies have also proven the effectiveness of technology-based education due to comprehensive access and cost-effectiveness [16][17][18][19][20][21][22][23][24][25][26][27][28]. As a result, due to the lack of theoretical and practical knowledge in the field of applying ICF for educational, research, and clinical purposes, it is suggested that future studies be conducted on educational policies, providing educational programs to specialists, and then evaluating their knowledge improvement to ensure the provision of correct and correct education.…”
Section: Principal Findingsmentioning
confidence: 99%